Financial performance of Brazilian agribusiness companies listed on B3 (Formerly BM&FBovespa): An analysis from 2007 to 2017 (Research, Society and Development, 2026)
Agribusiness plays a fundamental role in the Brazilian economy, contributing significantly to national production, exports, and employment generation. This study aims to analyze the financial performance profile of Brazilian agribusiness companies listed on BM&FBovespa between 2007 and 2017. The research adopts a descriptive and quantitative approach, using financial indicators related to indebtedness, liquidity, and profitability. The sample includes four companies operating in the agricultural segment: Brasilagro S.A., Pomifrutas S.A., Terra Santa Agro S.A., and SLC Agrícola S.A. The indicators analyzed include Total Debt, Short-Term Debt, General Liquidity, Return on Equity (ROE), and Net Margin. The results demonstrate that agribusiness companies are significantly influenced by climatic conditions, macroeconomic crises, and operational management decisions. In particular, the economic and climatic crisis of 2015–2016 had a substantial impact on the sector. However, most companies demonstrated resilience and recovery through technological investments, strategic restructuring, and improved financial management. The findings reinforce the importance of financial indicators as tools for evaluating corporate performance and understanding sectoral trends in Brazilian agribusiness.